Undecided Nation 2014
DOI: 10.1007/978-3-319-06480-2_8
|View full text |Cite
|
Sign up to set email alerts
|

The Costs and Benefits of Immigration Enforcement

Abstract: For more than two decades, the U.S. government has attempted to put a stop to unauthorized immigration from (and through) Mexico by implementing "enforcement-only" measures along the U.S.-Mexico border and at work sites throughout the country. These measures have not only failed to end unauthorized immigration, but have placed downward pressure on wages in a broad swath of industries. In recent decades, the U.S. government's avoidance of immigration reform and dependence upon enforcement-only approaches to imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Despite the oft-repeated claims that immigration harms the U.S. economy, researchers have suggested that immigration (including undocumented immigration) is a net economic positive by increasing tax revenue (Gardner, Johnson, and Wiehe, 2015), infusing new business and social capital (Light and Gold, 2000), and filling employment niches that complement native-born labor sectors (Hinojosa-Ojeda, 2010). Indeed, despite their legal exclusion from the labor market, a full 93 percent of working-age unauthorized immigrant men were in the labor force in 2009 (Donato and Armenta, 2011).…”
Section: Selection Network and Immigrant Revitalizationmentioning
confidence: 99%
“…Despite the oft-repeated claims that immigration harms the U.S. economy, researchers have suggested that immigration (including undocumented immigration) is a net economic positive by increasing tax revenue (Gardner, Johnson, and Wiehe, 2015), infusing new business and social capital (Light and Gold, 2000), and filling employment niches that complement native-born labor sectors (Hinojosa-Ojeda, 2010). Indeed, despite their legal exclusion from the labor market, a full 93 percent of working-age unauthorized immigrant men were in the labor force in 2009 (Donato and Armenta, 2011).…”
Section: Selection Network and Immigrant Revitalizationmentioning
confidence: 99%